2021
DOI: 10.3390/cells10030703
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Conditions Result in Trapping of PHF-Core Tau (297–391) Intermediates

Abstract: The self-assembly of tau into paired helical filaments (PHFs) in neurofibrillary tangles (NFTs) is a significant event in Alzheimer’s disease (AD) pathogenesis. Numerous post-translational modifications enhance or inhibit tau assembly into NFTs. Oxidative stress, which accompanies AD, induces multiple post-translational modifications in proteins, including the formation of dityrosine (DiY) cross-links. Previous studies have revealed that metal-catalysed oxidation (MCO) using Cu2+ and H2O2 leads to the formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…One known product of oxidation induced by Cu­(II) is dityrosine cross-links on proteins, such as Aβ . Dityrosine (DiY) formation, whereby closely spaced tyrosines covalently cross-link by ortho–ortho coupling at C3 of their benzene rings, has been used as a marker of oxidative stress, and DiY has been shown to form under Cu­(I/II)/H 2 O 2 oxidative conditions for Aβ and tau in vitro and within AD amyloid plaques in vivo . In the presence of H 2 O 2 , Cu­(II) induces dityrosine cross-linking more efficiently, serving as an excellent marker of oxidation .…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One known product of oxidation induced by Cu­(II) is dityrosine cross-links on proteins, such as Aβ . Dityrosine (DiY) formation, whereby closely spaced tyrosines covalently cross-link by ortho–ortho coupling at C3 of their benzene rings, has been used as a marker of oxidative stress, and DiY has been shown to form under Cu­(I/II)/H 2 O 2 oxidative conditions for Aβ and tau in vitro and within AD amyloid plaques in vivo . In the presence of H 2 O 2 , Cu­(II) induces dityrosine cross-linking more efficiently, serving as an excellent marker of oxidation .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Dityrosine (DiY) formation, whereby closely spaced tyrosines covalently cross-link by ortho–ortho coupling at C3 of their benzene rings, has been used as a marker of oxidative stress, and DiY has been shown to form under Cu­(I/II)/H 2 O 2 oxidative conditions for Aβ and tau in vitro and within AD amyloid plaques in vivo . In the presence of H 2 O 2 , Cu­(II) induces dityrosine cross-linking more efficiently, serving as an excellent marker of oxidation . Also, Cu­(II) is known to bind tau and induce tau oxidation, dimerization, and aggregation. , Recently, it was demonstrated that Cu­(II) alone or in the presence of H 2 O 2 induces oxidation and dityrosine cross-linking of a tau297–391 fragment which contains one tyrosine at position 310. , To further demonstrate the antioxidant ability of Salpyran , we performed a series of reactions using tau297–391 and Cu­(II) (1:10 ratio) in combination with H 2 O 2 to induce oxidation and dityrosine formation, which were quenched after 1 h with the addition of EDTA.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lysine methylation is part of the normal PTMs of tau in the human brain and can partially serve to protect against pathological tau aggregation [44] . Dityrosine (DiY) cross-links, another tau PTM induced by oxidative stress, was observed on human AD-derived tau oligomers and PHFs [45] . DiY cross-links of tau dGAE (tau297-391 fragment of the full-length tau) can facilitate the formation of non-toxic, soluble tau oligomers, inhibit the formation of β-sheets and further extension of prefibrils [46] , and increase the insolubility and stability of tau fibrils in AD [45] .…”
Section: Targeting the Post-translational Modifications Of Taumentioning
confidence: 99%